Polydeoxyribonucleotide Dermal Infiltration in Male Genital Lichen Sclerosus: Adjuvant Effects during Topical Therapy - Luigi Laino; Silvia Suetti; Isabella Sperduti (Dermatology Research and Practice)
Background. Lichen sclerosus (LS) is an autoimmune inflammatory skin disease that leads to tissue sclerosis. Actually, the first-line treatment consists of local steroid as clobetasol propionate (CP). Polydeoxyribonucleotide (PDRN) has demonstrated anti-inflammatory effects through the reduction of cytokine production and growth stimulation of fibroblast. Objective. To evaluate the efficacy of intradermal administration of PDRN in male patients suffering from genital lichen sclerosus in addition to topical 0.05% CP, as compared to administering 0.05% CP without PDRN injection. Patients/Methods. A group of male patients (n = 28; aged 25 to 65) suffering from LS were observed during topical therapy or subdermal in addition to topical therapy. Disease activity at baseline was evaluated on Investigator’s Global Assessment (IGA) and the Dermatology Life Quality Index (DLQI). We used polydeoxyribonucleotide in a commercial preparation for human use and a topical CP emulsion. Results. After therapy, in all group A patients there has been a regression of most of clinical pathological signs, while there has been a moderate improvement in all group B patients. Conclusions. On site intradermal administration of PDRN, associated with CP 0.05% cream, seemed to be associated with a clinical improvement of lichen sclerosus better than CP used in single therapy.